Composite dermis-fat graft and mucous membrane graft in severe contracted socket reconstruction - Manu Saini; Usha Singh; Surinder S Pandav; Manpreet Singh; Parul Chawla Gupta; Pankaj Gupta (Indian Journal of Ophthalmology, 2025)
The management of a severely contracted socket necessitates the restoration of fornix depth, the meticulous release of fibrotic components without compromising the already limited conjunctival tissue, and the replacement of lost volume. In this case series of four patients, the authors employed mucous membrane placement using the lid-splitting approach to address the deficit in fornix conjunctiva. This approach involved releasing posterior lamellar tension and repositioning the retractors at the fornix, followed by augmentation with a dermis-fat graft to restore volume.